Estudio De Calidad De Leche Realizado Durante La Pasantía En Dos Laboratorios De La Ciudad De Bogotá D.C (2023)
In the internship modality, support and collaboration activities were developed related to practices in the laboratory of Basic Sciences of the Antonio Nariño University, oriented to the implementation of knowledge acquired in the area of microbiology of Veterinary Medicine where different projects were carried out, among which is specifically the study of the "Evaluation of the in vitro effect of lysozyme and propolis on bacteria causing mastitis in cattle".